Performance analysis of ten brands of batteries for hearing aids - Penteado, Silvio Pires; Bento, Ricardo Ferreira (International Archives of Otorhinolaryngology, 2013)
Introduction: Comparison of the performance of hearing instrument batteries from various manufacturers can enable otologists, audiologists, or final consumers to select the best products, maximizing the use of these materials.Aim: To analyze the performance of ten brands of batteries for hearing aids available in the Brazilian marketplace.Methods: Hearing aid batteries in four sizes were acquired from ten manufacturers and subjected to the same test conditions in an acoustic laboratory.Results: The results obtained in the laboratory contrasted with the values reported by manufacturers highlighted significant discrepancies, besides the fact that certain brands in certain sizes perform better on some tests, but does not indicate which brand is the best in all sizes.Conclusions: It was possible to investigate the performance of ten brands of hearing aid batteries and describe the procedures to be followed for leakage, accidental intake, and disposal.
Keywords: Hearing Aids; Performance Tests; Benchmarking; Batteries; Reference Standards; Laboratory Equipment